2011
DOI: 10.1093/swr/35.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Parenting Processes Associated with Problem Behaviors: A Study of Adolescents in Santiago, Chile

Abstract: Considerable research in the U.S. has established that adolescent antisocial, aggressive, and attention problems have a negative influence on adolescents' ability to become productive members of society. However, although these behaviors appear in other cultures, little is known about the development of these problems among adolescents in countries other than the U.S.. This study contributes to our understanding of personality and parenting factors associated with adolescent problem behaviors using an internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…Its beneficial impact over time, therefore, can be understood through the gain in children's self-regulation process. Such a positive association with children's EF was illustrated in a recent study where attention problems of adolescents were related to their parents' monitoring (Bares, Delva, Grogan-Kaylor, & Andrade, 2011). Monitoring is also known to reduce children's likelihood of displaying behavioral problems (Crouter & Head, 2002;Sullivan, Childs, & O'Connell, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Its beneficial impact over time, therefore, can be understood through the gain in children's self-regulation process. Such a positive association with children's EF was illustrated in a recent study where attention problems of adolescents were related to their parents' monitoring (Bares, Delva, Grogan-Kaylor, & Andrade, 2011). Monitoring is also known to reduce children's likelihood of displaying behavioral problems (Crouter & Head, 2002;Sullivan, Childs, & O'Connell, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Rejection associated with frequent punishments increases aggressive tendencies in a child. It should be noted that all penalties used by a parent are treated as a sign of aggression towards an adolescent child, which is a kind of behaviour pattern that persists in the child as a habit of aggressive reacting to other people, objects or conflict situations (Wolińska, 2000;Poraj, 2002;Bares et al, 2011;Batool, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the presence of a warm, supportive mother may be more important in preventing violent behavior for adolescent women than for men (Blitstein et al, 2005). Interestingly, research utilizing a Chilean sample of adolescents found that less positive relationships with mothers were associated with higher levels of reported aggression for women than men (Bares et al, 2011). …”
Section: Gender Differences In Predictors Of Physical Aggressionmentioning
confidence: 99%